3D/4D echographic diagnosis of intracranial tumors in the fetus - S M Voevodin; T V Shemanaeva (IP Berlin A.V., 2016)
Anomalies of brain development is one of the first places in the structure of malformations in the fetus. The analysis of the volume of intracranial lesions of the brain using 3D/4D ultrasound techniques. Shown a poor prognosis in the presence of true brain tumors in fetuses. 3D/4D multipledata the technique of scanning is a highly informative approach for the differential diagnosis of intracranial neoplasms in the fetus.